Metabolic reprogramming during the Trypanosoma brucei life cycle - NOLAN, DEREK; Smith, Terry K.; Bringaud, Frédéric; Figueiredo, Luisa M. (My University, 2017)
Cellular metabolic activity is a highly complex, dynamic, regulated process that is influenced by numerous factors, including extracellular environmental signals, nutrient availability and the physiological and developmental status of the cell. The causative agent of sleeping sickness, Trypanosoma brucei, is an exclusively extracellular protozoan parasite that encounters very different extracellular environments during its life cycle within the mammalian host and tsetse fly insect vector. In order to meet these challenges, there are significant alterations in the major energetic and metabolic pathways of these highly adaptable parasites. This review highlights some of these metabolic changes in this early divergent eukaryotic model organism.
PUBLISHED
Keywords: Cellular metabolism; Trypanosoma brucei; Sleeping sickness; Immunology, Inflammation & Infection